KEPEMIMPINAN KEPALA DESA LEMPANGANG KABUPATEN GOWA DALAM MEMBERDAYAKAN MASYARAKAT PADA MASA COVID-19 PERSPEKTIF FIQH SIYASAH - Windasari, Sri; Halimang, St. (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
This study aims to find out how the leadership strategy of the Head of Lempangang Village in empowering the community during the Covid-19 pandemic. This research is a qualitative research with a syar'i, normative juridical, and sociological approach. The results showed that during the Covid-19 Pandemic, the Head of Lempangang Village launched several programs as a form of empowerment in dealing with the impact of Covid-19, including making pastries, making handicrafts and sewing courses as soft skills for economically affected residents. In addition to ensuring the safety of the lives (hifdz nafs) of each of its citizens from the Covid-19 virus, the village head is also responsible for the resilience of his residents economically to survive during and after the pandemic.